The Implementation of Good Corporate Governance at Indonesian Sharia Banks: A Review of Regulations and Legal Basis - Munir Munir; Rimi Gusliana Mais (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
The practice of Good Corporate Governance (GCG) in Islamic banking serves as a foundational element that goes beyond mere regulatory compliance, extending to the embedding of Sharia principles throughout all governance processes. This study seeks to evaluate how GCG is implemented at Bank Syariah Indonesia (BSI), assessing the extent to which its practices align with Indonesia’s national legal framework, including Law No. 21 of 2008, PBI No. 11/33/PBI/2009, as well as international standards such as the OECD guidelines and the ASEAN Corporate Governance Scorecard (ACGS). The research employs a literature review methodology with a descriptive-analytical approach, drawing from academic publications, relevant legislation, and BSI’s official reports for the 2023-2024 period. The results indicate that BSI has largely demonstrated strong adherence to core governance principles transparency, accountability, responsibility, independence, and fairness as evidenced by its “Highly Trusted” recognition under the CGPI and compliance with ISO 37301:2021 and ISO 37001:2016 standards. Nevertheless, challenges remain, including low public literacy on the Islamic economy, competition with conventional banks, a shortage of qualified human resources, and the need to harmonize Islamic law with national positive law. These findings contribute to the literature on Sharia GCG and offer practical recommendations for regulators and Islamic bank management.